Assessment of log‐based fingerprinting system of Mobius3D with Elekta linear accelerators. Issue 2 (27th November 2021) - Noh, Yu‐Yun; Kim, Jihun; Kim, Jin Sung; Shin, Han‐Back; Han, Min Cheol; Suh, Tae Suk
Abstract: Purpose: The purpose of this study was to investigate the matching error that occurs when the Mobius3D fingerprinting system is applied in conjunction with an Elekta linear accelerator (LINAC) and to offer an acceptable and alternative method for circumventing this problem. Material and methods: To avoid the multileaf collimator (MLC) conflicting error in the Mobius3D fingerprinting system, we developed an in‐house program to move the MLC in the Digital Imaging and Communications in Medicine (DICOM) radiotherapy (RT)‐Plan to pertinent positions, considering the relationship between log data and planned data. The re‐delivered log files were calculated in the Mobius3D system, and the results were compared with those of corrected data (i.e., we analyzed a pair of re‐collected log data and the previous DICOM RT‐Plan data). The results were then evaluated by comparing several items, such as point dose errors, gamma index (GI) passing rates, and MLC root‐mean‐square (RMS) values. Results: For the point dose error, the maximum difference found was below 2.0%. In the case of GI analysis of all plans, the maximum difference in the passing rates was below 1.4%. The statistical results obtained using a paired Student's t ‐test showed that there were no significant differences within the uncertainty. In the case of the RMS test, the maximum difference found was approximately 0.08 mm. Conclusions: Our results showed that all the mismatched log files were sufficiently acceptable within the uncertainty. We conclude that the matching error obtained when applying Mobius3D to an Elekta LINAC may be addressed using a simple modification of the fingerprinting system, and we expect that our study findings will help vendors resolve this issue in the near future.